Factors Affecting Lactation Performance of Deoni Cattle - G, Supriya; Patil, Vivek; Rathod, Prakash Kumar; Sagar, Vidya (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
The research was conducted on 78 lactation records of 78 Deoni cows over three years to analyze the effect of non-genetic factors on lactation performance traits. Data of lactation records were analyzed to determine the effect of age, parity, a period of calving and season of calving on lactation traits, viz., lactation milk yield (LMY), peak milk yield (PMY), lactation length (LL) and persistency of lactation. The findings revealed that age group and parity had a significant (p ≤0.05) effect on lactation milk yield, but not the period of calving and season of calving. Further, only the parity had a significant (P≤0.05) effect on peak milk yield of Deoni cattle but not the age group, period of calving, and season of calving. The other two traits, namely lactation length, and persistence was not influenced significantly by any the non-genetic factors evaluated in Deoni cattle.